Kinematic analysis of basketball free throw trajectory - Kelmendi, D.; Miftari, F.; Shaqiri, K.; Dedi, T. (SportMont, 2025)
Free throw shooting is a fundamental skill in basketball that requires a combination of technique, consistency, mental focus, and the ability to perform under pressure. The purpose of this study was to analyze the kinematic parameters of the ball trajectory during a successful free throw. The study involved 20 players from the Kosovo Basketball League during the 2020 season. Ten kinematic variables were selected for analysis. Three Canon cameras (Canon Inc., Tokyo, Japan), recording at 60 frames per second, were used to capture the free throw motion. The recorded videos were analyzed using the Ariel Performance Analysis System (APAS) to extract kinematic data. Significant correlations were found between kinematic variables in the ball trajectory during a successful free throw between: Initial distance between the ball and the center of gravity and height of release (r=0.68), Final distance between the ball and the center of gravity and height of release (r=0.61), Height of release and vertical displacement of the ball`s trajectory (r=-0.72), Release angle and entry angle of the ball (r=0.65). The results of this research enrich the scientific knowledge of the kinematic analysis of the ball trajectory in basketball free throws, contributing to the development of more accurate methodologies for evaluating and improving performance in the sport of basketball. These findings contribute to a deeper understanding of the kinematic principles underlying successful free throw shooting and provide valuable information for coaches and athletes seeking to enhance performance.